Finishing occlusion, degree of stahility and the PAR index - Woods Michael; Lee Doug; Crawford Edward (Sciendo, 2000)
The occlusions of sixty -five patients, treated by one private specialist orthodontist with consistent philosophy and goals, were assessed according to the PAR Index. For each patient, pre-treatment, post-treatment and follow-up study models were assessed. Follow-up models were taken at least 6.5 years following the removal of all retention appliances. Mean-weighted PAR scores were calculated for the total sample and various sub-groups at each stage. Mean percentage changes in weighted PAR scores were also calculated. The relationships between the occlusal standards at the end of active treatment and at the end of the follow-up period, and specific diagnostic and treatment factors were then investigated to search for any factors that might be predictive of long-term post-treatment occlusal stability or instability.